2018
DOI: 10.1155/2018/4248792
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Guided Capsule Endoscopy in the Diagnosis of Gastrointestinal Diseases in Minors

Abstract: Objective This study aimed at investigating the clinical value of magnetic-guided capsule endoscopy (MGCE) in the diagnosis of gastrointestinal diseases in minors. Methods Eighty-four minor patients hospitalized in the pediatric department at Ruijin Hospital between June 2015 and January 2018 were enrolled for this study. Following bowel preparation, all patients underwent MGCE. The feasibility, safety, diagnostic yield, and sensitivity of MGCE were analyzed. Patients were followed up for more than 2 weeks. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Further developments in the field of MACE include automation, the Ankon system (Ankon Optoelectronic Technology Co. Ltd, China) utilizes a computer controlled robotic arm, which can be either directly controlled or adopt a pattern of programmed movements. This has been used in a variety of populations, with promising results (29)(30)(31)(32). There are no direct comparisons between this robotically controlled system and the MiroCam Navi system, however studies using these systems that examined the ability to pull the capsule past the pylorus, suggested whilst this was not possible with a hand held magenet it could be achieved with the Ankon system, suggesting stronger or more effective magnetic capture (10,33).…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Further developments in the field of MACE include automation, the Ankon system (Ankon Optoelectronic Technology Co. Ltd, China) utilizes a computer controlled robotic arm, which can be either directly controlled or adopt a pattern of programmed movements. This has been used in a variety of populations, with promising results (29)(30)(31)(32). There are no direct comparisons between this robotically controlled system and the MiroCam Navi system, however studies using these systems that examined the ability to pull the capsule past the pylorus, suggested whilst this was not possible with a hand held magenet it could be achieved with the Ankon system, suggesting stronger or more effective magnetic capture (10,33).…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Furthermore, MGCE as a non-invasive procedure is well tolerated by pediatric patients. After scanning the stomach, MGCE still has enough battery power to record clear images of the entire small bowel ( Xie et al, 2019 ; Qian et al, 2018 ; Lai et al, 2020 ). MRE is preferred for pediatric CD patients because no ionizing radiation is involved, with high soft tissue contrast and a low incidence of adverse events (( Rimola et al, 2011 ; Hokama et al, 2020 ; Minordi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, MGCE overcomes this disadvantage. The capsule can be manipulated within the magnetic field generated by an external remote control device ( Qian et al, 2018 ) to translate, flip, and move up and down in the patient’s stomach. Likewise, MGCE also plays an important role in detecting lesions in the terminal ileum.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a clinical study in Ruijin Hospital Affiliated to Shanghai Jiaotong University recruited 84 minor patients hospitalized in the pediatric department who underwent MCCG examinations, with an average age of 12 ± 3:2 years. The results showed that the diagnosis rate of MCCG for gastric diseases was 13.1%, the sensitivity was 13.1%, and no adverse events occurred [41]. To explore the feasibility and safety of the application of MCCG in children, a retrospective study in Shanghai Children's Hospital included 129 children with gastrointestinal symptoms who needed gastroscopy but were unwilling or unable to tolerate routine gastroscopy (including painless gastroscopy), aged 6 to 14 years old, with an average of 9:8 ± 1:9 years old.…”
Section: Robotic-type Mccementioning
confidence: 91%